Sequential tendon ruptures in ochronosis: case report - Kumar, E. G. Mohan; Kumar, G. M. Yathisha (International Journal of Research in Orthopaedics, 2017)
Alkaptonuria is a rare autosomal recessive disorder characterised by the absence of homogentisic acid oxidase, due to deficiency of an enzyme that degrades HGA in the tyrosine degradation pathway. Homogentisic acid (HGA) and its metabolites accumulate in the connective tissues leading to dark pigmentation of connective tissue in patients with alkaptonuria. HGA deposits in connective tissue causes weakness of the tendon and subsequent rupture, especially the large tendons in the body. Only few cases are reported in the literature with multiple tendon rupture but many case reports are available with isolated rupture of tendons. We report on a patient with sequential tendon ruptures in a patient. The case is reported for its rarity.